Analisis Hubungan Antar Parameter Kualitas Crude Palm Oil di PT. Laguna Mandiri Rantau Factory - Tri Ayu Novelena; Noer Komari (Jurnal Natural Scientiae, 2022)
Analysis of the relationship between the quality parameters of crude palm oil (CPO) at PT. Laguna Mandiri Rantau Factory using a simple linear regression method and multiple linear regression has been carried out. This study was to determine the free fatty acid content, water content, and gross content of CPO and to compare the sample with company standards and SNI. The relationship between parameters was modeled with a simple linear regression mathematical model, Y = a + bx and multiple linear regression, Y = a + b1X1 + c2x2… + bnXn. The results showed that the average free fatty acid was 4.02%, the water content was 0.18%, and the impurities content was 0.018%. The fatty acid content has not met the company standard, while the water content and impurities have met the company and SNI. The relationship of water content (X) to free fatty acids (Y) in the equation Y = 3.328 + 3.804x. The relationship of free fatty acids (X) to water content (Y) in the equation Y = - 0.808 + 0.246x. The relationship between impurities (X) and free fatty acids (Y) in the equation Y = 3.569 + 25.399x. The relationship of free fatty acids (X) to the level of impurities (Y) in the equation Y = -0.124 + 0.035x. The relationship between dirt content (X) and water content (Y) in the equation Y = 0.070 + 6.315x. The relationship between water content (X) and dirt content (Y) in the equation Y = - 0.007 + 0.135x. The relationship of water content (X1) and dirt content (X2) to free fatty acids (Y) in the equation Y = 3.391 + 2.542 X1 + 9.344 X2. The relationship of impurities (X1) and free fatty acids (X2) to water content (Y) in the equation Y = - 0.737 + 0.572 X1 + 0.226X2. The relationship of free fatty acids (X1) and water content (X2) to the level of impurities (Y) in the equation Y = - 0.107 + 0.030X1 + 0.021X2.